Dexmedetomidine inhibits the NF-κB pathway and NLRP3 inflammasome to attenuate papain-induced osteoarthritis in rats - Fang Cheng; Feng-Feng Yan; Yue-Peng Liu; Yan Cong; Ke-Fu Sun; Xue-Ming He (Taylor & Francis Group, 2019)
Context: Dexmedetomidine (Dex) has been reported to have an anti-inflammatory effect. However, its role on osteoarthritis (OA) has not been explored. Objective: This study investigates the effect of Dex on OA rat model induced by papain. Materials and methods: The OA Wistar rat model was induced by intraluminal injection of 20 mL of papain mixed solution (4% papain 0.2 mL mixed with 0.03 mol L−1 l-cysteine 0.1 mL) into the right knee joint. Two weeks after papain injection, OA rats were treated by intra-articular injection of Dex (5, 10, or 20 μg kg−1) into the right knee (once a day, continuously for 4 weeks). Articular cartilage tissue was obtained after Dex treatment was completed. Results: The gait behavior scores (2.83 ± 0.49), PWMT (15.2 ± 1.78) and PTWL (14.81 ± 0.92) in H-DEX group were higher than that of OA group, while Mankin score (5.5 ± 0.81) was decreased (p < 0.05). Compared with the OA group, the IL-1β (153.11 ± 16.05 pg mg−1), IL-18 (3.71 ± 0.7 pg mg−1), IL-6 (14.15 ± 1.94 pg/mg) and TNF-α (40.45 ± 10.28 pg mg−1) levels in H-DEX group were decreased (p < 0.05). MMP-13, NLRP3, and caspase-1 p10 expression in Dex groups were significantly lower than that of OA group (p < 0.05), while collagen II was increased (p < 0.05). p65 in the nucleus of Dex groups was significantly down-regulated than that of OA group (p < 0.05). Discussion and Conclusions: Dex can improve pain symptoms and cartilage tissue damage of OA rats, which may be related to its inhibition of the activation of NF-κB and NLRP3 inflammasome.